Intelligent techniques in recommendation systems contextual advancements and new methods - Dehuri, Satchidananda; IGI Global (Hershey, Pa. : IGI Global (701 E. Chocolate Avenue, Hershey, Pennsylvania, 17033, USA), 2012)
'This book is a comprehensive collection of research on the latest advancements of intelligence techniques and their application to recommendation systems and how they could improve this field of study'--Provided by publisher.
A recommender system supporting teachers to author learning sessions in decision-making / Arnoldo Rodruez -- Building efficient assessment applications with personalized feedback: a model for requirement specifications / Constanta-Nicoleta Bodea, Maria-Iuliana Dascalu -- Building recommender systems for network intrusion detection using intelligent decision technologies / Mrutyunjaya Panda, Manas Ranjan Patra, Sachidananda Dehuri -- REPERIO: a flexible architecture for recommendation in an industrial context / Frank Meyer ... [et al.] -- Risk evaluation in the insurance company using REFII model / Goran Klepac -- Intelligent techniques in recommender systems and contextual advertising: novel approaches and case studies / Giuliano Armano, Alessandro Giuliani, Eloisa Vargiu -- Revisiting recommendation systems: development, lacunae, and proposal for hybridization / Sagarika Bakshi ... [et al.] -- A fuzzy clustering approach for segmenting retail industry / M. Hemalatha -- Rough web intelligent techniques for page recommendation / H. Inbarani, K. Thangavel -- Hybrid neural architecture for intelligent recommender system classification unit design / Emmanuel Buabin -- Newly developed nature-inspired algorithms and their applications to recommendation systems / Utku K$1'Xu(Be -- Modelling clearance sales outshopping behaviour using neural network model / M. Hemalatha -- Hybrid neural genetic architecture: new directions for intelligent recommender system design / Emmanuel Buabin -- Web usage mining approaches for web page recommendation: a survey / H. Inbarani, K. Thangavel.s
Includes bibliographical references.
Also available in print.
Mode of access: World Wide Web.
Description based on title screen (IGI Global, viewed October 9, 2012).
Keywords: Decision support systems; Evolutionary algorithms; Hybrid approaches; Industrial applications; Intelligent techniques; Neural networks; Recommendation systems; Swarm intelligence